STUDI PERESAPAN AIR HUJAN DI KOTA DENPASAR - Suharta, I Ketut; Merit, Nyoman; Sunarta, Nyoman (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 2)
The first aim of this research is to know the capacity of infiltration and the capacity of percolation in the area ofDenpasar city. The second things is to know how much the water of rainfall potential to be infiltrated in Denpasar city.Capacity of infiltration and capacity of percolation tested by using the double ring infiltrometer with innercylinder diameter is 30 cm and outer cylinder is 50 cm. Volume of potential infiltrated rain water calculated bymultiplied the rainfall by catchment area and coefficient of infiltration.The findings show that the capacity of infiltration is about 0.05 mm/hour to 0.211 mm/hour, and the capacity ofpercolation is about 0.125 mm/hour to 0.471 mm/hour. Potential volume of infiltration of rain water is 25,405,028.77m3/year, it mean that about 10 % of total rainfall volume, 252,560,182.68 m3/year, so about 227,155,153.91 m3/year willbe a potential to increasing the surface run off.Based on the findings the following suggestions can be made: (1) further research should be done with the dept ofpercolation test should be about 2 m, and 20 cm above the water table; (2) it is necessary to infiltrate rainwater alltogether by the community of the city of Denpasar, by using a hole of 2 m3 each 100 m2 area.
Keywords: infiltration, percolation, potential of rain water infiltration